The rise of executive federalism: Implications for the picket fence and IGM - Thompson, Frank J. (2013)
The ascendance of federal grants to states and localities as a major tool of government action has fueled scholarly interest in building a better theory of intergovernmental management (IGM). It has also spawned an enduring metaphor, "picket-fence federalism," which has done much to shape thinking about the context and nature of IGM. More recently, however, a competing conceptual lens called "executive federalism" (EF) has emerged. Proponents of this perspective contend that administrative discretion looms increasingly large in shaping who gets what from federal grants, that vastly greater dependence on program waivers has driven this development, and that political executives--both elected and appointed--play a growing role in the administration of grant programs. To the degree that the EF lens accurately captures developments, it challenges the conceptual and empirical underpinnings of both the picket-fence model and IGM. This article provides a preliminary test of the EF perspective by examining the case of Medicaid. It charts a research agenda that would more fully probe the implications of EF for a theory of IGM. - Reproduced.
Keywords: Federalism